Progressive damage analysis of woven composite panels subjected to tensile loading - Kamarulazizi, Sulaiman (2012)
A research on the progressive damage analysis subjected to tensile load for woven composite plates is conducted using the finite element method. A progressive failure algorithm is employed in the finite element to model damage and material nonlinearity in the woven composite laminates. In order to achieve this, three types of stress based failure criteria namely Tsai-Wu, Tsai Hill and maximum stress are included in the finite element analysis via user subroutines which is coded in FORTRAN programming language and is then linked with ABAQUS finite element software. Series of coupon tests are carried out for C-glass/epoxy, carbon/epoxy, and hybrid carbon/C-glass/epoxy laminates according to ASTM3039 to obtain their mechanical and strength properties which are required as input parameters in the finite element analysis. The finite element progressive damage analyses are performed on flat composite laminates made of C-glass/epoxy, carbon/epoxy, and hybrid carbon/C-glass/epoxy which are clamped on one end and free on the other end. It is observed that the results obtained from the finite element analysis using the three failure criteria are in excellent agreement with the experimental results. Glass sample with orientation (0,0,0,0)s and (0,90,0,90)s shows that Tsai-Wu is the best failure theory when compared to the experimental result. Comparison between first ply failure and total failure found that for the case of flat plates the differences in the first ply failure load and ultimate failure loads are very small which is less than 10% over range between 0 to 90 degrees of fiber layup orientations. Visual inspections of the damage specimens using microscopic camera LEICA MS5 are also carried out for certain type of composite laminates mentioned above to investigate the mode of failures. From the inspections it was observed that in general all of the samples exhibit almost similar types of failure modes such as fiber breakage, delamination, and matrix cracking. Finally, a progressive damage analysis of woven hybrid stiffened plates under tension is conducted to investigate the load carrying capabilities up to total failure as well as the energy absorption capabilities for various types of fiber orientations. Fourteen different types of angle ply layup have been studied with the conclusion that layup orientation of (0,90)4 has the highest maximum load of 33209.4N and energy absorption of 1048.49 J/kg while ((45)4,(-45)4) has the lowest maximum load of 6506.7N and (75)8 has the lowest energy absorption of 185.37 J/kg. The comparison between first ply failure and total failure of the laminates found that between the ranges of 0 to 90 degree ply layup, 45 degree angle ply has the highest percentage difference of 35.72% for maximum load and 32.39% for energy absorption between first ply failure and final ply failure. (0)8 and (90)8 degree ply layup shows no difference between first ply failure and final ply failure which indicates that this type of layup has the characteristic of a very brittle material.